Effect of turmeric starch, lecithin, and canola oil supplements on waffles quality - Nguyễn Minh Thủy; Hong Van Hao; Le Chau Mong THU; Tran Ngoc Giau; Vo Quoc Tien; Ngô Văn Tài; N.V. Thanh (Food Science and Technology, 2023)
This study aimed to produce waffles with increased quality by adding turmeric starch (1–2%), lecithin (0.6–1%), and canola oil (7.5–12.5%) to the recipe. The physicochemical characteristics and sensory values of the product were analyzed together with radical scavenging activity (DPPH% testing). Multiple regression was used to analyze the relationship between curcumin in waffles/firmness and three independent variables (turmeric starch, lecithin, and canola oil), with the goal of using the independent variables to predict the dependent variables. Response surface methodology was used to optimize the content of the dependent variables to obtain the highest curcumin content and the best firmness. Being formulated with the optimal values of turmeric starch (2%), lecithin (0.86%), and canola oil (11.2%), waffles contain the optimal curcumin content (5.84 mg/100 g) and a good texture (not too hard or too soft at 209.7 g force). An amount of 100 g of waffles contain 6.90 g of protein, 36.64 g of carbohydrates, 16.78 g of lipids, 3.8 g of resistant starch, 1.32 g of fiber, and 0.6 g of ash. Analysis results of total polyphenolic content and 2,2-diphenyl-1-picryl-hydrazyl (DPPH) inhibition were also found, with 37.81 mg GAE/100 g and 27.25% DPPH inhibition, respectively. The product was also highly appreciated for its sensory properties.
Keywords: Nanocomposite Films for Food Packaging; Phytochemicals and Antioxidant Activities; Meat and Animal Product Quality